Phylogenetic and mitochondrial genome analysis of a putative new cave cricket species (Rhaphidophoridae) from a Thai subterranean habitat - KITTIYA INCHOEDCHAY; SOMJIT HOMCHAN; YASH MUNNALAL GUPTA (Society for Indonesian Biodiversity, 2025)
Abstract. Inchoedchay K, Homchan S, Gupta YM. 2025. Phylogenetic and mitochondrial genome analysis of a putative new cave cricket species (Rhaphidophoridae) from a Thai subterranean habitat. Biodiversitas 26: 3855-3862. Cave crickets (family Rhaphidophoridae) are a unique group of orthopteran insects characterized by long legs, large hind legs, elongated antennae, a humped back body, and are wingless, adaptations that enable them to thrive in subterranean environments such as caves. Despite their ecological importance and unique adaptations, their mitochondrial genomic architecture remains poorly characterized. This study investigates the mitochondrial genome of a cave cricket from the family Rhaphidophoridae, commonly referred to as cave crickets. Specifically, this research presents the first complete mitochondrial genome assembly and annotation of a morphologically distinct cave cricket specimen systematically collected from Nam Sai Cave, Noen Maprang District, Phitsanulok Province, Thailand. Using high-throughput sequencing and bioinformatics tools, a 16,260 base pair mitochondrial genome was assembled, comprising 37 genes, including 13 protein-coding genes, 22 tRNA genes, and 2 rRNA genes, with a GC content of 25.57%. The mitochondrial genome exhibits the identical gene arrangement of Orthoptera, suggesting strong conservation across the order. Phylogenetic analysis placed the specimen within the subfamily Aemodogryllinae, revealing a close evolutionary relationship with the genera Diestrammena, Tachycines, and Diestramima, strong molecular and morphological evidence supporting its classification within the tribe Aemodogryllini. These findings provide new genomic data for putative new species in Rhaphidophoridae, offering valuable insights into their phylogenetic relationships, genetic diversity, and adaptations to cave environments. This study lays the foundation for future taxonomic revisions and comparative evolutionary analyses within the family.